Activities of Ufa Branch of Russian Society for Care of Refugees in 1915-1917 - O. S. Pavlova (Научный диалог)
The article is devoted to the main activities of the Ufa branch of the Russian society for the care of refugees in 1915-1917. The author points out that military actions in the First World War had caused a mass evacuation of the population of the frontline areas affected by the military actions in the rear of the governorate of the Russian Empire, also in Ufa governorate. Based on regional materials the experience of the organization of assistance to victims of war by the diocesan clergy is considered, which consisted in the collection of funds, provision of housing, organization of educational process for refugee children, etc. Initiative of the Ufa division of the Russian Society for the care of refugees was the opening of three warehouses in Ufa, Belebey and Menzelinsk to supply the refugees with clothes, and on their basis houses for the homeless was open, providing employment and income for women refugees. Special attention the clergy paid to the problem of meeting the spiritual needs of the refugees by organizing the preaching work of local diocesan clergy, and by priests of the diocese of Chelm evacuated to Ufa governorate invited for this purpose by Society. The study of the experience of the Ufa branch of the Russian Society for the care of refugees has led to the conclusion that the diocesan clergy along with public institutions and local organizations made a contribution to the solution of problems of resettlement of the refugee population in the governorate.